2009
DOI: 10.1111/j.1365-2710.2009.01060.x
|View full text |Cite
|
Sign up to set email alerts
|

Problems associated with prophylactic use of erythromycin in 1566 staff to prevent hospital infection during the outbreak of pertussis

Abstract: These results indicate that EM appears to cause adverse effects more frequently than reported in the package insert in Japan. The prophylactic use of EM for pertussis infection is recognized in the guideline of the Centers for Disease Control and Prevention. However, this study suggests that attention should be paid to EM non-compliance during a pertussis outbreak, which could extend the duration of the outbreak and increase the number of affected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In Japan, prophylactic administration of erythromycin caused adverse effects such as digestive organ symptoms, diarrhea, stomachache and abdominal distention in hospital staffs in 2009. It suggested that attention should be paid to erythromycin compliance during a pertussis outbreak (25). …”
Section: Discussionmentioning
confidence: 99%
“…In Japan, prophylactic administration of erythromycin caused adverse effects such as digestive organ symptoms, diarrhea, stomachache and abdominal distention in hospital staffs in 2009. It suggested that attention should be paid to erythromycin compliance during a pertussis outbreak (25). …”
Section: Discussionmentioning
confidence: 99%
“…While studies have demonstrated the effectiveness of PEP at preventing secondary transmission of pertussis [14][15][16][17][18], available data have focused primarily on erythromycin which, compared to the newer macrolide azithromycin, is less commonly used because it requires a longer treatment course and has a less favorable side effect profile, resulting in lower compliance [19][20][21][22]. It is also unclear whether PEP is needed in the setting of pertussis vaccination, despite waning vaccine-induced immunity [18].…”
Section: Introductionmentioning
confidence: 99%